Urgensi Sadar Lingkungan di Era Teknologi - Juanda Tiolopan Hutahaean; Masduki Asbari; Freddy Nurwanto (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to find out how to encourage the younger generation to innovate and provide impacts and solutions, not only for society, but also for the environment. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Achmad Zaky's YouTube channel entitled "Green Technology for Sustainable Future" which he explained. The results of this study explain that we must not forget the importance of caring for the environment when technology is developing.